The Short Stress State Questionnaire in German (SSSQ-G): A Multi-Study Validation - Ringgold, Veronika; Shields, Grant S.; Hauck, Felicitas; Kurz, Miriam; Schindler-Gmelch, Lena; Abel, Luca; Richer, Robert; Eskofier, Björn; Rohleder, Nicolas (European Journal of Health Psychology, 2024)
Background: Although the physiological stress response is well established, self-reported stress has received less attention. Some validated measures assess task-related stress via self-report in English. However, no such measure exists in Germany. Aims: To address this research gap, we translated and validated the Short Stress State Questionnaire in German (SSSQ-G). It assesses stress-related affective states (e.g., anger) and appraisals (e.g., feelings of control). We expected to replicate the factor structure of the English SSSQ in the SSSQ-G. Methods: We included the SSSQ-G in five studies that induced stress either via the gold standard task for acute stress induction – the Trier Social Stress Test (TSST) – or via a novel virtual reality (VR) task. The sample consisted of 213 participants (112 women; age: 23.36 ± 3.62 years). Results: The SSSQ-G demonstrated sensitivity to stress-induced changes (ps < .01), particularly in response to the TSST compared to the VR stress induction (p < .001 for total scale comparison between stressors). In TSST participants, the magnitudes of stress-induced changes on the SSSQ-G were larger than those on the Positive and Negative Affect Schedule (PANAS), p = .008, indicating strong construct validity. Although the SSSQ-G total score was highly reliable (α = .85, Ω = .86), factor analyses revealed a six-factor solution, with the factors representing Distress, Worry, Confidence, Negative affect, Motivation, and Self-evaluation. Limitations: The SSSQ-G appears more sensitive to state changes induced by moderate-to-severe stress tasks. Conclusion: The SSSQ-G is a reliable and valid instrument for assessing states of subjective stres